1915 N.H. Laws 180-81 - (:unkn) unknown (My University, 1915)
An Act to Revise and Amend the Fish and Game Laws, ch. 133, pt. 2, § 18: Prohibited the setting of a spring gun. Punished by a fine of $50-500.
Keywords: TRAP GUNS